Etched track profiles for relativistic 7 GeV silicon and 17.48 GeV Nickel ions in PADC detector: The case study of convex track walls. (October 2021) - Fromm, M.; Abu-Shady, M.; Groetz, J.E.; Awad, E.M.
Abstract: 650 μm thick PADC foils are exposed to 7 GeV Silicon and 17.48 GeV Nickel accelerated ions at particle fluence of about 1000 cm −2 . The relativistic ions passed through the entire thickness of the PADC foils and created latent tracks that were etched sequentially under strong etching conditions (NaOH + ethanol). For each time sequence, etched track profiles were found by carefully polishing the detector edge, and then imaged in order to measure their geometrical parameters (diameter and length). Track wall curvature study allows for better understanding of the physico-chemical interactions undertaken during the etching process. Etched track profiles have the distinctive feature of presenting concave walls near to the track aperture. Such special feature is likely to be due to a depth dependent variation of the bulk etch rate (Vb ). This depth dependence is investigated and discussed. A simulation program has been written based on the variational principle, it uses experimentally determined variable Vb and a constant specific track etch rate (Vt ). Simulations results are in good agreement with experimental micrographs both qualitatively and quantitatively. Such case study may show promise as a means of fabricating controlled shape pores in polymer membranes. Highlights: 7 GeV Silicon and 17.48 GeV Nickel ion tracks are etched in 650 μm thick PADC. Etched track profiles exhibit convex track walls - Depth-dependent bulk etch-rate is invoked. Phits & Fluka MC simulations invalidate the assumption of dose - bulk etch rate relation. Etched track profile simulations are in excellent agreement with experimental data. Structural inhomogeneity along the first 0–60 μm may be due to PADC polymerisation.